An Integrated Hydrologic Modeling and Data Assimilation Framework. - Kumar, Sujay; Peters -Lidard, Christa; Yudong Tian; Reichie, Rolf; Geiger, James; Alonge, Charles; Eylander, John; Houser, Paul (Computer (00189162), 2008)
The article discusses the Land Information System (LIS), a multiscale infrastructure for hydrologic modeling and data assimilation which was developed by the United States' National Aeronautics & Space Administration. LIS integrates satellite and ground-based observations and land-surface modeling methods to support applications that can be used in water-resource and agricultural management, statistical weather prediction, and assessment of air quality and military mobility. The discussion focuses on the features of a land data assimilation system such as its software architecture and high-computing technology, its modularity, reusability, extensibility, and inversion control, and its Earth system modeling standards.